PENINGKATAN LITERASI ARTIFICIAL INTELLIGENCE MAHASISWA MELALUI KEGIATAN KULIAH UMUM “AI FOR BUSINESS: TRANSFORMASI STRATEGI, INOVASI, DAN KEUNGGULAN KOMPETITIF DI ERA DIGITAL ” - Nabila Maisara; Wira Bharata (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The rapid advancement of Artificial Intelligence (AI) requires higher education institutions to equip students with relevant digital competencies. This article describes the implementation and evaluates the effectiveness of a public lecture entitled "AI for Business: Strategy Transformation, Innovation, and Competitive Advantage in the Digital Era," organized by the Business Administration Study Program, FISIP Mulawarman University. The event was attended by 70 students from the Class of 2025 using an expert-driven lecture method combined with interactive discussion. Pre-test and post-test evaluation revealed significant improvements: AI comprehension in a business context increased by 21.2%, interest in learning AI rose by 10.9%, and the average participant score improved from 3.97 (Good) to 4.35 (Very Good). The activity effectively enhanced students' AI literacy and digital work readiness, while supporting the university's Key Performance Indicators and SDG 4 (Quality Education).